Analysis of COVID-19 Concerns Raised by the Construction Workforce and Development of Mitigation Practices - Bou Hatoum, Makram; Faisal, Ali; Nassereddine, Hala; Sarvari, Hadi (Frontiers in Built Environment, 2021)
The coronavirus outbreak has created a global health crisis that has disrupted all industries, including the construction industry. Following the onset of the pandemic, construction workers faced and continue to face unprecedented safety and health challenges. Therefore, construction employers established new safety precautions to protect the health and safety of the workforce and minimize the spread of the virus. The new precautions followed the advice and guidelines offered by different health and safety agencies like the Occupational Safety and Health Administration (OSHA), Centers of Disease Control and Prevention (CDC), and the Associated General Contractors of America (AGC). With construction projects resuming operations, it becomes important to analyze the coronavirus-related health and safety concerns of construction workforce and understand how the new safety procedures can assist on jobsites. Existing studies mostly focused on interviews and surveys with construction companies to understand the impact on project performance and supply chains. However, no study has yet to analyze the U.S. construction workforce. This paper fills the gap by providing a qualitative descriptive analysis of the COVID-19 complaints data gathered by OSHA from construction jobsites. Information gathered by OSHA includes the jobsite location, the North American Industry Classification System (NAICS) of the construction company, the type of the complaint (i.e., formal or non-formal), and a thorough description of the complaint. N-grams were employed to analyze the complaints, detect trends, and compile a list of the most frequent concerns reported by the workforce. The analysis of the complaints data identifies safety practices that were most violated, highlights major safety and health concerns for construction workers, and pinpoints geographical areas that have seen a surge in complaints. The study also synthesized the existing research corpus and compiled a list of 100 best practices that construction employers can adopt to mitigate the concerns of the workforce. The findings of this study provide insights into the safety and health trends on construction sites, lay the foundation for future work of academicians and practitioners to address the concerns faced by construction workers, and serve as lessons learned for the industry in the case of any future pandemic.